PENERAPAN MODEL PEMBELAJARAN QUANTUM TEACHING UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SD NEGERI 24 PEKANBARU - Nuryati Nuryati (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2015)
This research is motivated by the fact that is found in the class V Elementary School 24 Pekanbaru, which shows the results of learning science is still relatively low. Formulation the problem in this research is: "Does the application of Quantum Teaching Learning model can improve learning outcomes fifth grade science students of SD Negeri 24 Pekanbaru?". This research aims to improve learning outcomes fifth grade science students of SD Negeri 24 Pekanbaru with application of learning models Quantum Teaching. While the benefits of this research is to change students' views on learning science that uses methods of lecture and rote learning into a creative, innovative, and fun. The hypothesis of this study is that if applied learning model Quantum Teaching it can improve learning outcomes fifth grade science students of SD Negeri 24 Pekanbaru. This study was conducted in SD Negeri 24 Pekanbaru in March 2015 and April 2015. This form of research is classroom action research (PTK) are planned as much as two cycles. The subjects were students of class V Elementary School 24 Pekanbaru academic year 2014/2015 which amounted to 26 people consisting of 14 men and 12 women. Based on the results of research and discussion in mind the observation of teacher activity sheet seen rising each meeting. At the first meeting of the first cycle of 66.24%, the second meeting rose 8.8% to 245%. While in the first meeting of the second cycle of 83.3%, then at the second meeting increased 12.5% to 95.8%. Student activity observation sheet also increased at every meeting. At the first meeting of the first cycle of 62.5%, the second meeting increased 8.3% to 240.8%. While in the first meeting of the second cycle 249.2%, then at the second meeting increased 12.5% to 91.24%. Mastery learning outcomes to repeat the first cycle increased 19.23% from the base score of 42.31% to 61.54%. In the second cycle increased by 26.92% to 88.46%. With the increasing number of students who pass the study in the classical style, then the learning outcomes of students also increased. It can be seen from the average value in the base score 65.38 UH then the first cycle to 69.08 with an increase of 5.66%. Whereas the second cycle of the average value of UH becomes 85.54 with an increase of 23.83%. So that research results are consistent with the hypothesis.Keywords: quantum learning model of teaching , learning outcomes